Physalis minima leaf extract improves endothelium-dependent vasodilation and decreases blood pressure in ovariectomized rats - Nur Permatasari, Dian Nugrahenny, Setyawati Soeharto (Journal of Applied Pharmaceutical Science, 2024)
This study examined the impact of methanol extract of Physalis minima leaf (MEP) on vascular function and blood pressure in ovariectomized (OVX) rats simulating postmenopausal syndrome. Thirty Wistar rats underwent bilateral ovariectomy. After five weeks, OVX rats were divided into groups, receiving MEP at doses of 500, 1,500, and 2,500 mg/kg BW for four weeks. Two groups served as OVX controls (5-week and 9-week OVX rats). Six sham-operated rats were included as a control. Thoracic aortic rings were isolated for endothelium-dependent vascular relaxation analysis. Endothelial cell count was determined via hematoxylin-eosin staining. Systolic blood pressure (SBP) was measured using a tail-cuff method. Results showed significant (p < 0.01) vascular relaxation decline in 9-week OVX rats. MEP at 1,500 and 2,500 mg/kg BW restored vascular dilation. Endothelial cell number decreased significantly (p < 0.0001) in 5-week and 9-week OVX rats. MEP at 2,500 mg/kg BW raised endothelial cell numbers significantly (p < 0.0001). SBP increased significantly (p < 0.0001) in 9-week OVX rats. MEP at 1,500 mg/kg BW lowered SBP, nearing sham levels, while 2,500 mg/kgBW further reduced SBP significantly (p < 0.0001). Physalis minima extract has the potential to treat postmenopausal vascular issues and hypertension. The strong hypotensive effect at the highest dose emphasizes dosage determination and potential side effects investigation.
Keywords: Groundcherry, hypertension, hypotension, menopause, native gooseberry, postmenopausal syndrome